2015
DOI: 10.1093/nar/gkv1114
|View full text |Cite
|
Sign up to set email alerts
|

SATPdb: a database of structurally annotated therapeutic peptides

Abstract: SATPdb (http://crdd.osdd.net/raghava/satpdb/) is a database of structurally annotated therapeutic peptides, curated from 22 public domain peptide databases/datasets including 9 of our own. The current version holds 19192 unique experimentally validated therapeutic peptide sequences having length between 2 and 50 amino acids. It covers peptides having natural, non-natural and modified residues. These peptides were systematically grouped into 10 categories based on their major function or therapeutic property li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 59 publications
2
104
0
Order By: Relevance
“…In BRENDA [20], compounds are queried independently based on sequences in three-letter code. Specialized databases of peptides, such as the BIOPEP database of bioactive peptides [94] or SATPdb (Insitute of Microbial Technology, Chandigargh, India) [44], are also used. SATPdb is a metabase with links to peptide data in other databases, such as the AHTPDB (Insitute of Microbial Technology, Chandigargh, India) [18] database of peptides inhibiting angiotensin I-converting enzyme (EC 3.4.15.1).…”
Section: Navigating the Network Of Links And Cross-links Between Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In BRENDA [20], compounds are queried independently based on sequences in three-letter code. Specialized databases of peptides, such as the BIOPEP database of bioactive peptides [94] or SATPdb (Insitute of Microbial Technology, Chandigargh, India) [44], are also used. SATPdb is a metabase with links to peptide data in other databases, such as the AHTPDB (Insitute of Microbial Technology, Chandigargh, India) [18] database of peptides inhibiting angiotensin I-converting enzyme (EC 3.4.15.1).…”
Section: Navigating the Network Of Links And Cross-links Between Dmentioning
confidence: 99%
“…The lipophilicity profile of GRAS compounds, a key property in predictions of bioavailability for humans, was particularly similar to that of the approved drugs. The above approach was expanded [96] by searching for information about GRAS compounds in other databases, including the SuperScent database of flavor compounds (Charité—Universitätsmedizin Berlin, Germany) [44] and the TCM database (Laboratory of Computational and Systems Biology, China Medical University, Taichung, Taiwan) of natural products used in traditional Chinese medicine [47]. The results of the analysis revealed that the structure and physicochemical properties of selected flavor-enhancing ingredients are similar to those of analgesics and satiety agents.…”
Section: Application Of Databases In Analyses Of Datasets and Intementioning
confidence: 99%
“…2 Bioactive peptides have the potential to play a prominent role in human health by affecting the digestive system, endocrine functions, cardiovascular risk, immune response and nervous systems, 3 and infant growth and development through several lactational stages. 4 Publicly accessible databases such as Biopep, 5 StraPep, 6 STAPdb, 7 PepBank 8 and others continuously update the knowledge on biologically active food peptides with physiological significance beyond their pure nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…We applied the tool to in‐house experimentally derived CD4 + restricted epitopes, however the tool is equally applicable to CD8 + T‐cell epitopes, as shown for the IEDB‐derived data set. In addition to the epitopes, the tool can also be applied to cluster and explore interesting patterns in any linear peptide data set (such as cell‐penetrating peptides, tumour homing peptides, haemolytic peptides, therapeutic peptides).…”
Section: Discussionmentioning
confidence: 99%